2011
DOI: 10.1111/j.1365-2044.2011.06914.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro suppression of drug‐induced methaemoglobin formation by Intralipid® in whole human blood: observations relevant to the ‘lipid sink theory’*

Abstract: SummaryTo provide further evidence for the lipid sink theory, we have developed an in vitro model to assess the effect of Intralipid Ò 20%on methaemoglobin formation by drugs of varying lipid solubility. Progressively increasing Intralipid concentrations from 4 to 24 mg.ml )1 suppressed methaemoglobin formation by the lipid soluble drug glyceryl trinitrate in a dose-dependent manner (p < 0.001). Both dose and timing of administration of Intralipid to blood previously incubated with glyceryl trinitrate for 10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Therefore, lipid treatment resulted in lower aqueous bupivacaine concentration, lower myocardial content and better cardiac performance. Samuels et al 20 assessed the efficacy of partitioning by measuring the production of methemoglobin in blood by drugs of varying lipid solubility. Adding lipid emulsion substantially reduced methemoglobin production caused by the most lipid soluble drug, but did not suppress methemoglobin production caused by less lipid soluble drugs.…”
Section: Mechanismmentioning
confidence: 99%
“…Therefore, lipid treatment resulted in lower aqueous bupivacaine concentration, lower myocardial content and better cardiac performance. Samuels et al 20 assessed the efficacy of partitioning by measuring the production of methemoglobin in blood by drugs of varying lipid solubility. Adding lipid emulsion substantially reduced methemoglobin production caused by the most lipid soluble drug, but did not suppress methemoglobin production caused by less lipid soluble drugs.…”
Section: Mechanismmentioning
confidence: 99%
“…Lipid emulsion also substantially reduced methemoglobin production caused by the three most lipid soluble drugs tested, but not by the other less lipid soluble ones in vitro [19]. Recently, enhanced decrease of the concentration of bupivacaine in multiple organs including the brain and heart by lipid emulsion was shown in rats and in a physiologically based pharmacokinetic model [13,20].…”
Section: Mechanismmentioning
confidence: 96%
“…9 Direct evidence in support of this theory includes data showing that lipid emulsions bind large amounts of local anesthetic in vitro. 12 Another study showed that by using a drug's partition coefficient (a measure of the difference in solubility of a compound in hydrophilic and hydrophobic environments) and volume of distribution, one could accurately predict the decrease of in vitro serum concentrations of 11 drugs after the addition of lipid emulsion. In this study, plasma samples underwent ultracentrifuging.…”
Section: Understanding the Mechanismmentioning
confidence: 99%